No Safe Haven: Operation Condor and Transnational Repression in South America. - Lessa, Francesca; Balardini, Lorena (International Studies Quarterly, 2024)
Transnational repression, i.e. the deliberate targeting of refugees and dissidents by states across borders, is a relatively understudied subject in international relations. This article analyzes why states act together to persecute political opponents abroad and explains variations in such practices. It proposes a theory of cooperation in transnational repression and uses the case study of Operation Condor in the 1970s to test it. Through Operation Condor, South American authoritarian states willingly forewent key aspects of their sovereignty to establish a sophisticated system of cooperation to target dissidents abroad. This scheme was a critical extension of these countries' domestic-level policies of repression against political opposition and enabled them to target politically active refugees wherever they were located. Exiles were perceived as constituting an existential threat to these autocracies' survival, given their ability to potentially undermine both their internal and external regime security, which therefore warranted their elimination. We draw on an interdisciplinary methodology, which combines archival research, interviews, trial observation, and the analysis of legal verdicts, alongside conclusions derived from our novel dataset, the Database on South America's Transnational Human Rights Violations (1969–1981).